A Victorian Curate : A Study of the Life and Career of the Rev. Dr John Hunt. - Yeandle, David (Cambridge, UK : Open Book Publishers, 2021)
A Victorian Curate: A Study of the Life and Career of the Rev. Dr John Hunt is an absorbing personal account of the corruption and turmoil in the Church of England at this time. It will appeal to anyone interested in this history, the relationship between science and religion in the nineteenth century, or the role of the curate in Victorian England.
The Funeral. -- Bibliography -- Select Works by John Hunt -- Other Works Cited -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books